2021
DOI: 10.1200/jco.20.02259
|View full text |Cite
|
Sign up to set email alerts
|

Melflufen and Dexamethasone in Heavily Pretreated Relapsed and Refractory Multiple Myeloma

Abstract: PURPOSE Melphalan flufenamide (melflufen) is a first-in-class peptide-drug conjugate that targets aminopeptidases and rapidly and selectively releases alkylating agents into tumor cells. The phase II HORIZON trial evaluated the efficacy of melflufen plus dexamethasone in relapsed and refractory multiple myeloma (RRMM), a population with an important unmet medical need. PATIENTS AND METHODS Patients with RRMM refractory to pomalidomide and/or an anti-CD38 monoclonal antibody received melflufen 40 mg intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 36 publications
4
115
0
Order By: Relevance
“…A recent multicenter, international, open-label, phase I–II study showed that melflufen is active in patients with relapsed and refractory MM (RRMM). These results demonstrate the feasibility of this scheme and support the initiation of additional clinical studies with melflufen in MM, both in combination with dexamethasone and in triplet with additional drug classes [ 139 , 140 ]. In a Phase I study, the established maximum tolerated dose was 40 mg melflufen plus dexamethasone.…”
Section: Attempts To Find a “Better Melphalan”supporting
confidence: 59%
“…A recent multicenter, international, open-label, phase I–II study showed that melflufen is active in patients with relapsed and refractory MM (RRMM). These results demonstrate the feasibility of this scheme and support the initiation of additional clinical studies with melflufen in MM, both in combination with dexamethasone and in triplet with additional drug classes [ 139 , 140 ]. In a Phase I study, the established maximum tolerated dose was 40 mg melflufen plus dexamethasone.…”
Section: Attempts To Find a “Better Melphalan”supporting
confidence: 59%
“…It also demonstrated that melflufen is equally effective in melphalan-naïve and melphalan-refractory patients [52]. The second study, focusing on heavily pretreated RRMM, showed that melflufen combined with dexamethasone leads to clinical improvement in the triple-class RRMM population with an overall response rate of 26%, median progression-free survival of 3.9 months, and median overall survival of 11.2 months [53]. In this study, we demonstrated that melflufen is highly effective at targeting plasma cells, particularly in samples from RRMM patients, including those with poor prognostic markers, such as del 17p or t(4;14).…”
Section: Discussionmentioning
confidence: 96%
“…The next-generation melphalan pro-drug melflufen (melphalan flufenamide ethyl ester) is an alkylating agent that has shown its high efficacy. It was recently approved by the FDA for use in combination with dexamethasone in R/R MM patients [219]. Melflufen enters cells where it is targeted by aminopeptidases resulting in its trapping in organelles and membranes allowing its accumulation.…”
Section: Discussionmentioning
confidence: 99%